Analysis of the influence of tax understanding and taxpayer compliance on tax revenue perception among MSMEs in Ciomas District at KPP Pratama Ciawi - Deswita Puji Lestari; Mahwiyah Mahwiyah (Privietlab, 2026)
This study investigates the influence of tax understanding and taxpayer compliance on the perception of tax revenue among micro, small, and medium enterprises located in Ciomas District and registered at the local tax office. The research employs a quantitative approach using a structured questionnaire to capture respondents’ views regarding their knowledge of tax obligations and their compliance behavior. The analysis reveals that taxpayer compliance plays a meaningful role in shaping positive perceptions of tax revenue, while tax understanding shows a weaker contribution when assessed individually. However, both factors collectively strengthen the overall perception of the effectiveness of tax revenue management. The findings highlight the importance of continuous tax education and supportive compliance strategies to enhance trust and awareness among small business taxpayers. This study contributes to the understanding of behavioral aspects of taxation within the MSME sector